Water and Climate Change : Impacts on Groundwater Resources and Adaptation Options - Clifton, Craig (World Bank, Washington, DC, 2017)
Adaptation to climate impacts on groundwater resources in developed and developing countries has not received adequate attention. This reflects the often poorly understood impacts of climate change, the hidden nature of groundwater and the general neglect of groundwater management. Many developing countries are highly reliant on groundwater. Given expectations of reduced supply in many regions and growing demand, pressure on groundwater resources is set to escalate. This is a crucial problem and demands urgent action. This report addresses the impacts of climate change on groundwater and adaptation options. The Earth's climate is projected to become warmer and more variable. Increased global temperatures are projected to affect the hydrologic cycle, leading to changes in precipitation patterns and increases in the intensity and frequency of extreme events; reduced snow cover and widespread melting of ice; rising sea levels; and changes in soil moisture, runoff and groundwater recharge. Increased evaporation and the risk of flooding and drought could adversely affect security of water supply, particularly surface water. Due to these pressures, as well as global population growth, demand for groundwater is likely to increase.